Superfecundation and superfetation with resulting heteropaternal twins--a possible resolution of the phenomena in the era of DNA typing - Raczek, Ewa (Archiwum medycyny sądowej i krjminologii, 2003)
In this paper a bibliography on superfecundation and superfetation phenomena and the author's opinion on the subject was presented.In this paper a bibliography on superfecundation and superfetation phenomena and the author's opinion on the subject was presented.